Post-error Recruitment of Frontal-Sensory Cortical Projections Promotes Attention in Mice - Norman, Kevin J. (Neuron, 2021)
The frontal cortex, especially the anterior cingulate cortex area (ACA), is essential for exerting cognitive control after errors, but the mechanisms that enable the modulation of attention to improve performance after errors are poorly understood. Here, we demonstrate that during a mouse visual attention task, ACA neurons projecting to the visual cortex (VIS; ACA(VIS)) are recruited selectively by recent errors. Optogenetic manipulations of this pathway collectively support that rhythmic modulation of ACA(VIS) projection neurons in anticipation of visual stimuli is crucial for adjusting performance following errors. 30Hz optogenetic stimulation of ACA(VIS) in anesthetized mice recapitulates the increased gamma and reduced theta VIS oscillatory changes that are associated with endogenous post-error performance during behavior, and subsequently increased visual-evoked spiking, a hallmark feature of visual attention. This frontal-sensory neural circuit links error monitoring with implementing adjustments of attention to guide behavioral adaptation, pointing to a circuit-based mechanism for promoting cognitive control.